2014
DOI: 10.1186/1866-1955-6-44
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep and behavior in autism spectrum disorder (ASD): a review

Abstract: Although there is evidence that significant sleep problems are common in children with autism spectrum disorder (ASD) and that poor sleep exacerbates problematic daytime behavior, such relationships have received very little attention in both research and clinical practice. Treatment guidelines to help manage challenging behaviors in ASD fail to mention sleep at all, or they present a very limited account. Moreover, limited attention is given to children with low-functioning autism, those individuals who often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
236
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(249 citation statements)
references
References 80 publications
9
236
1
3
Order By: Relevance
“…21 Sleep Problems: Sleep problems occur more frequently in patients with ASD than in typically developing patients and are strongly associated with daytime I/PB, among other problems. 22 Although more research is needed, many clinicians have anecdotal experience with improvement in I/PB after treatment of sleep problems. 22 Promotion of sleep hygiene in children with sleep problems should be prioritized.…”
Section: Step 5a Assess and Address Any Current Medical Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Sleep Problems: Sleep problems occur more frequently in patients with ASD than in typically developing patients and are strongly associated with daytime I/PB, among other problems. 22 Although more research is needed, many clinicians have anecdotal experience with improvement in I/PB after treatment of sleep problems. 22 Promotion of sleep hygiene in children with sleep problems should be prioritized.…”
Section: Step 5a Assess and Address Any Current Medical Problemsmentioning
confidence: 99%
“…22 Although more research is needed, many clinicians have anecdotal experience with improvement in I/PB after treatment of sleep problems. 22 Promotion of sleep hygiene in children with sleep problems should be prioritized. 23 The ATN has a useful packet to help parents improve their child's sleep habits (https:// www.…”
Section: Step 5a Assess and Address Any Current Medical Problemsmentioning
confidence: 99%
“…Mannion & Leader (2014) reviewed these studies and reported a range of prevalence rates from 33% (Goldman et al, 2011) to 80.9% (Mannion, Leader & Healy, 2013). Sleep difficulties include time getting to sleep and night-waking, but at the clinical level sleep disorders are predominantly described as insomnia (Cohen et al, 2014) or as 'unspecified' (Malow et al, 2016). The review by Cohen and colleagues (2014) attempted to unpick some of the relationships between sleep and behaviour in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Only one paper included in Cohen et al (2014) reported on verbal skills (Taylor et al, 2012). One reason for this omission may be that not all children with ASD are felt to have linguistic difficulties (DSMV, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation